Tradisi Mallanca pada Masyarakat Belawae di Desa Ajang Pulu Kabupaten Bone - Asnidar A. (Rayhan Intermedia, 2018)
This study aims to determine the perception, value and social changes in the implementation of the Mallanca tradition for the community Belawae District Sibulue of Bone Regency. This research used observation, interview and documentation method. The results showed that the community considers that the tradition of Mallanca is a tradition from generation to generation conducted by Belawae people who are ingrained. Although hard but no resentment between one player and the other. Because fostering the ropes of brotherhood and become a place of friendship. The noble cultural values ​​which up to now are maintained by society can be derived from social values, cultural values ​​and religious values. Changes that occur are basically only a few things that are material only. However, his spiritual aspect remained unchanged.